TELADAN MARIA DALAM INJIL LUKAS 1:38 DAN RELEVANSINYA BAGI PERKEMBANGAN IMAN UMAT BERIMAN - Prasojo Adi Wibowo; Antonius Virdei Eresto Gaudiawan (Bahasa Indonesia, 2018)
The Church is an assembly of faithful who believe to Christ. Mary is a mother of Church, especially as a faith’s example. Her faith is full of submit and believe to God, and create love for the life of world. She is a model for the Church because of thankfullness of gift from God that integrate with feel disposed to be a servant for people. Her obedience faith and pious life become an example of life to people of God until now. Mary’s will to submit her life become means of salvation in God’s salvation plan has been written in the Gospel of Luke 1: 38 “I am the servant of God, may it be to me as you say”. She is fully dedicate as God’s servant her self with born Word who reincarnate become human. Jesus and Mary become a new Adam and Eve to redeem an ancentor’s sin in heaven.